Concurrent Deep Brain Stimulation Reduces the Direct Cortical Stimulation Necessary for Motor Output. Issue 12 (11th September 2020) - Weaver, Kurt E.; Caldwell, David J.; Cronin, Jeneva A.; Kuo, Chao‐Hung; Kogan, Michael; Houston, Brady; Sanchez, Victor; Martinez, Vicente; Ojemann, Jeffrey G.; Rane, Swati; Ko, Andrew L.
ABSTRACT: Background: Converging literatures suggest that deep brain stimulation (DBS) in Parkinson's disease affects multiple circuit mechanisms. One proposed mechanism is the normalization of primary motor cortex (M1) pathophysiology via effects on the hyperdirect pathway. Objectives: We hypothesized that DBS would reduce the current intensity necessary to modulate motor‐evoked potentials from focally applied direct cortical stimulation (DCS). Methods: Intraoperative subthalamic DBS, DCS, and preoperative diffusion tensor imaging data were acquired in 8 patients with Parkinson's disease. Results: In 7 of 8 patients, DBS significantly reduced the M1 DCS current intensity required to elicit motor‐evoked potentials. This neuromodulation was specific to select DBS bipolar configurations. In addition, the volume of activated tissue models of these configurations were significantly associated with overlap of the hyperdirect pathway. Conclusions: DBS reduces the current necessary to elicit a motor‐evoked potential using DCS. This supports a circuit mechanism of DBS effectiveness, potentially involving the hyperdirect pathway that speculatively may underlie reductions in hypokinetic abnormalities in Parkinson's disease. © 2020 International Parkinson and Movement Disorder Society